Atividades experimentais em bioquímica básica: um estudo baseado na resolução de problemas em diferentes níveis de ensino - Figueira, Angela Carine Moura (2014)
The Problem Based Learning (PBL) can be a valuable tool in Science Teaching, encouraging curiosity and motivation of the student. In this thesis we use PBL trying to help the teaching of basic biochemistry. The first step of this study was to investigate the students' preconceptions about proteins, sugars and lipids, which helped us to guide both the proposed activities in the didactic notebook What We eat and We drink? as the discussions in the classroom during the application of those activities. The population studied was quite broad, covering the ninth year of Elementary School, first, second and third years of High School as well as students of the Course of Chemistry of the Federal University of Santa Maria. In general we can say that proteins are seen by students as important substances for maintaining a healthy lifestyle, while sugars and fats are seen as harmful and cause diseases. Examples of how to apply the PBL both in Basic as Higher Education, are shown in the form of articles and in them we can see that those activities are quite challenging. It is common that students initially feel uncomfortable when working with an experimental resolution of the issue on which they don t received a ready protocol. However, it is heartening to see the progress of students to participate in this methodology, which allows us to state that PBL should be more widely disseminated and implemented in the classroom, in many different levels of education.